The Analysis of Product Differentiation & Brand Awareness on Interest in Becoming a Customer of Commercial Islamic Bank - Dewi Fatmasari; Dikdik Harjadi; Nida Putri Awalia; Azizi Abu Bakar (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2025)
Islamic banking is one type of banking activity whose activities are based on sharia principles, which aims to be free from usury. However, in its development it has experienced obstacles, especially in the field of marketing. So that the right strategy is needed, so that Islamic banking can be accepted by the community. In this case, in order to win the competition, it must create a product that is different from similar products, this difference is called product differentiation. In addition, the company can raise public awareness of its existence with a positive and innovative impression through the products offered. The purpose of this study is to determine the effect of product differentiation and brand awareness on the interest in becoming a customer of Bank Muamalat Indonesia. The method used in this study is descriptive analysis with a quantitative approach. While the number of samples in this study was 100 respondents. The data analysis tool used was Multiple Linear Regression Analysis. The results of this study show that product differentiation and brand awareness together influence the interest in becoming a customer; (2) product differentiation has a positive effect on purchasing interest; (3) brand awareness has a positive effect on purchasing interest.